The effect of green tea leaf on broiler’s performance, blood profiles, and immunity - Qui, NH; Linh, NT; Thu, NTA (Journal of the Hellenic Veterinary Medical Society, 2025)
Green tea leaf powder (GT) is used as a therapeutic supplement in humans and animals worldwide. The aim of this study was to evaluate the effects of GT on growth performance and carcass characteristics, including meat color, breast pH, cooking loss, immune response, and blood profile. The study, which included 120 local broiler chickens, was conducted using a completely randomized design with five treatments with different levels of GT in diet (0; 0.1; 0.2; 0.3; 0.4%). The results showed that GT (0.4 %) markedly improved body weight and body weight gain, while reducing feed intake and the feed conversion ratio. The effectiveness of GT in the diets was evident in improving carcass characteristics, including breast and thigh weights, compared to the control treatment (P < 0.05). The treatment with 0.4% GT resulted in the highest immune organ indices. GT increased the antibody titers of birds at 47 d and 85 d (P < 0.05). Although GT slightly enhanced the index of serum protein and decreased cholesterol levels, this study did not find any changes in the blood profiles (P > 0.05). Thus, the application of 0.4% GT to the diet can improve the growth performance and health of broiler chickens.